All Days 2009
DOI: 10.2118/119600-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brine Salinity on Interfacial Tension in Arab-D Carbonate Reservoir, Saudi Arabia

Abstract: Carbonate reservoirs contain more than 50% of the worlds's hydrocarbons reserves. In Saudi Arabia, most of the current hydrocarbon production is from Arab-D carbonate reservoir (Upper Jurassic limestone). Oil production started 50 years ago. So, the various fields had been subjected to prolonged pressure support by waterfloods (since 1970) using high salinity brine (Arabian Gulf water). Oil recovery using waterflooding is about a third of the oil original in place (OOIP); while two-thirds still remain as a tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 3 publications
5
38
0
Order By: Relevance
“…A trendline was drawn for each category to generalize the behaviour of brines in that category. Category 1 shows a decreasing trend of IFT, similar to that observed by Okasha and Alshiwaish (2009). These authors studied the effect of salinity on IFT and concluded that the decrease in salt concentration from 200,000 mg/L to 50,000 mg/L did reduce the IFT.…”
Section: Ift Results Of Different Brines At 20°csupporting
confidence: 73%
“…A trendline was drawn for each category to generalize the behaviour of brines in that category. Category 1 shows a decreasing trend of IFT, similar to that observed by Okasha and Alshiwaish (2009). These authors studied the effect of salinity on IFT and concluded that the decrease in salt concentration from 200,000 mg/L to 50,000 mg/L did reduce the IFT.…”
Section: Ift Results Of Different Brines At 20°csupporting
confidence: 73%
“…For example, in a study by Al‐Sahhaf et al on IFT measurement of n ‐octane/brine solution, it was revealed that the IFT values are linearly dependent on parameters such as pressure, temperature, and salt concentration. By inspecting the obtained results from the effect of salinity on the IFT of aqueous/crude oil solutions, some contradictory results can be addressed . For example, Firoozabadi and Ramey measured the IFT between brine and three reservoir oils.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the concentration of inorganic solid particles on the water/oil interface, R/As ratios there are other factors likes the salinity, PH and well head pressure. In spite of salts can have a pronounced effect on the IFT of crude water /oil system, (Bai et al, 2010), and pH significantly affected the film-forming, oil-wetting and emulsion-stabilizing properties of the polar asphaltene and resin fractions Okasha, et al 2009. Unfortunately no considerable difference on the salinity concentration and PH could be seen for the four crude samples under lab test (see table 1).…”
Section: Demulsifier Dosage and Emulsion Temperaturementioning
confidence: 93%